Circadian clock control of interactions between eIF2α kinase CPC-3 and GCN1 with ribosomes regulates rhythmic translation initiation - Ebimobowei O. Preh; Manuel A. Ramirez; Sidharth Mohan; Chanté R. Guy; Deborah Bell-Pedersen (Proceedings of the National Academy of Sciences, 2025)
Misregulation of the activity of GCN2, the kinase that phosphorylates and inactivates translation initiation factor eIF2α, has been implicated in several health disorders, underscoring the need to determine the mechanisms controlling GCN2 activation. During nutrient starvation, increased uncharged tRNA levels trigger GCN1 and GCN20 proteins to mediate the binding of uncharged tRNA to GCN2 to activate the kinase to phosphorylate eIF2α. Under constant conditions, activation of the Neurospora crassa homolog of GCN2, CPC-3, is controlled by the circadian clock. However, how the circadian clock controls the rhythmic activity of CPC-3 was not known. We found that the clock regulates CPC-3 and GCN1 interaction with ribosomes and show that these interactions are necessary for clock regulation of CPC-3 activity. CPC-3 activity rhythms, and the rhythmic interaction of CPC-3 and GCN1 with ribosomes, are abolished in a temperature-sensitive valyl-tRNA synthetase mutant ( un-3 ts ) that has high levels of uncharged tRNA Val at all times of the day. Disrupting the interaction between GCN1 and uncharged tRNA in the absence of GCN20 altered rhythmic CPC-3 activity, indicating that the clock controls the interaction between uncharged tRNA and GCN1. Together, these data support that circadian rhythms in mRNA translation through CPC-3 activity require rhythms in uncharged tRNA levels that drive the rhythmic interaction between CPC-3 and GCN1 with ribosomes. This regulation uncovers a fundamental mechanism to ensure temporal coordination between peak cellular energy levels and the energetically demanding process of mRNA translation.